Classroom Quality and Academic School Readiness Outcomes in Head Start: The Indirect Effect of Approaches to Learning. Issue 1 (2nd January 2019) - Bustamante, Andres S.; Hindman, Annemarie H.
ABSTRACT: This study used the FACES 2009 dataset to examine the possibility of an indirect effect of classroom quality on academic school readiness through teacher-rated approaches to learning in a large nationally representative sample of children served by Head Start. Research indings: Classroom quality did not directly predict gains in academic school readiness across the Head Start school year (β = -0.009, p = .844). However, classroom quality did predict gains in teacher-rated approaches to learning (β = 0.151, p = .040), which in turn predicted gains in academic school readiness (β = 0.105, p < .001), and there was a significant indirect effect of classroom quality on academic school readiness through approaches to learning (β = 0.016, p = .049). Although associations were generally small, this pattern of results suggests that approaches to learning may facilitate the relationships between classroom quality and academic school readiness. Practice or Policy: Educators should make targeted efforts to boost children's approaches to learning as it may represent an important lever for academic success. In a society increasingly focused on high-stakes testing, we must not lose sight of the importance of domain-general skills that can help children achieve school and life success.